Joint venture breakup and the exploration-exploitation trade-off - Ngo Van Long; Antoine Soubeyran; Raphael Soubeyran (Fondazione Eni Enrico Mattei (FEEM), 2009)
This paper explores the effect of a potential joint-venture breakup on the level of technology transfer in a set-up with exploration-exploitation trade-offs in the presence of time compression costs. We consider a joint-venture relationship between a technologically advanced multinational firm and a local firm operating in a developing economy where the ability to enforce contracts is weak, and the local firm can quit without penalties. The multinational firm has to consider the advantages and disadvantages of an intensive transfer of technology versus an extensive one. In response to the breakup incentives, the multinational firm reduces the intensity (lowering the pace) and opts for a more extensive transfer mode (longer duration of transfer), compared to the first best. The scheme is supported by a flow of side payments to encourage the local firm to stay longer. We show that a fall in time compression costs may increase or decrease the intensity of technology transfer, both in the first-best and in the second-best scenarios, depending on the nature of the saving in time-compression costs.
Keywords: F23; D23; O33; O34; 330; Technology transfer; joint venture; absorptive capacity; time-compression cost; breakup of relationship